2017
DOI: 10.5811/westjem.2017.4.33018
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Urolithiasis in the Presence and Absence of Microscopic Hematuria in the Emergency Department

Abstract: IntroductionUrolithiasis is a common medical condition that accounts for a large number of emergency department (ED) visits each year and contributes significantly to annual healthcare costs. Urinalysis is an important screening test for patients presenting with symptoms suspicious for urolithiasis. At present there is a paucity of medical literature examining the characteristics of ureteral stones in patients who have microscopic hematuria on urinalysis versus those who do not. The purpose of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…Patients presenting with acute renal colic at the emergency department Authors Year Country Study design No. of patients % Male Mean age ± SD (years) Kim et al [ 13 ] 2018 South Korea Retrospective, observational 798 68.6 48.2 ± 13.3 Desai et al [ 14 ] 2018 USA Retrospective, observational 350 NR NR Türk and Ün [ 15 ] a 2017 Turkey Prospective, observational 516 60.5 37 ± 20.3 Shrestha et al [ 16 ] a 2017 Nepal Retrospective, observational 201 55.2 29 ± 13.5 Odoemene et al [ 17 ] a 2017 Nigeria Prospective, observational 69 76.8 40.4 ± 2.9 Mefford et al [ 18 ] 2017 USA Retrospective, observational 393 69 Median 43 (IQR 32–54) Rapp et al [ 19 ] 2016 USA Retrospective, observational 613 47 49 ± 0.6 Park et al [ 20 ] 2016 South Korea Prospective, RCT 103 66 45.6 ± 12.55 Hernandez et al [ 21 ] 2016 USA Retrospective, observational 536 56 45.9 ± 16.3 <...>…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients presenting with acute renal colic at the emergency department Authors Year Country Study design No. of patients % Male Mean age ± SD (years) Kim et al [ 13 ] 2018 South Korea Retrospective, observational 798 68.6 48.2 ± 13.3 Desai et al [ 14 ] 2018 USA Retrospective, observational 350 NR NR Türk and Ün [ 15 ] a 2017 Turkey Prospective, observational 516 60.5 37 ± 20.3 Shrestha et al [ 16 ] a 2017 Nepal Retrospective, observational 201 55.2 29 ± 13.5 Odoemene et al [ 17 ] a 2017 Nigeria Prospective, observational 69 76.8 40.4 ± 2.9 Mefford et al [ 18 ] 2017 USA Retrospective, observational 393 69 Median 43 (IQR 32–54) Rapp et al [ 19 ] 2016 USA Retrospective, observational 613 47 49 ± 0.6 Park et al [ 20 ] 2016 South Korea Prospective, RCT 103 66 45.6 ± 12.55 Hernandez et al [ 21 ] 2016 USA Retrospective, observational 536 56 45.9 ± 16.3 <...>…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al [ 13 ] found negative microhematuria in patients with lower stones or elevated serum blood urea nitrogen (BUN). Mefford et al [ 18 ] showed an increased prevalence of hydronephrosis in patients with urolithiasis and negative microhematuria. As hydronephrosis is easy to screen with ultrasonography, Daniel et al [ 60 ] developed the STONE PLUS Score with addition of point-of-care ultrasound of the kidney to the original STONE Score.…”
Section: Discussionmentioning
confidence: 99%
“…Mefford et al [18] showed an increased prevalence of hydronephrosis in patients with urolithiasis and negative microhematuria. As hydronephrosis is easy to screen with ultrasonography, Daniel et al [60] developed the STONE PLUS Score with addition of point-of-care ultrasound of the kidney to the original STONE Score.…”
Section: Discussionmentioning
confidence: 98%
“…Similar a otros reportes donde indican como complicaciones más frecuentes infección, hematuria y obstrucción de la vía urinaria (hidronefrosis). Cabe recalcar que es importante tener presente posibles diagnósticos diferenciales según cada caso (3)(4)(5)8) y la mayoría de casos en hidronefrosis no se produce hematuria por lo que el examen de orina sería normal (13) .…”
Section: Discussionunclassified